1991
DOI: 10.1007/bf01826056
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive quantification of superior mesenteric artery blood flow during sympathoneural activation in normal subjects

Abstract: The role of the splanchnic circulation in normal subjects during sympathoneural activation induced by stimuli which either raise (mental arithmetic, cold pressor test, isometric exercise) or maintain (head-up tilt) blood pressure has been studied by measuring superior mesenteric artery blood flow using a noninvasive Doppler ultrasound method in 18 normal subjects. Cardiac, systemic and regional haemodynamic changes were simultaneously studied. Blood pressure rose with the pressor tests and was maintained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 9 publications
2
19
2
Order By: Relevance
“…This result is consistent with the Wndings of previous studies (Chaudhuri et al 1991;Hayashi et al 2006;Kuipers et al 2008), and conWrms partly that performing a mental task induces vasoconstriction in the splanchnic artery. Chaudhuri et al (1992) reported that the Fig.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This result is consistent with the Wndings of previous studies (Chaudhuri et al 1991;Hayashi et al 2006;Kuipers et al 2008), and conWrms partly that performing a mental task induces vasoconstriction in the splanchnic artery. Chaudhuri et al (1992) reported that the Fig.…”
Section: Discussionsupporting
confidence: 94%
“…The blood Xow in the superior mesenteric artery (SMA), which mainly supplies the small intestine, decreases and/or its vascular resistance increases relative to resting levels in response to a mental task (Chaudhuri et al 1991(Chaudhuri et al , 1992Hayashi et al 2006;Kuipers et al 2008). Murray et al (2004) also reported that rectal mucosal blood Xow is decreased by performing a psychological task.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with this view, Yu and Blessing (161) proposed that the cutaneous vasoconstriction that is initially evoked is associated with cerebral vasodilation, such that cerebral blood flow is increased at a time when the salience of the stimulus needs to be assessed. Regardless of the physiological significance of the initial orienting reflex, however, it has long been known that more prolonged threatening stimuli typically elicit a more complex autonomic response, which is characterized by an increase in arterial blood pressure, cardiac output, and heart rate, together with marked vasoconstriction in renal and mesenteric vascular beds and usually also vasodilation in skeletal muscle beds, in both humans (6,14,27,34,60,68,75,95,99,119,157) (Fig. 1) and animals (24,65,106,155).…”
Section: Pattern Of Cardiovascular and Respiratory Responses To Stresmentioning
confidence: 99%
“…The method is reproducible, has been validated and correlates well with results of invasive studies (Clark et al, 1980;Chaudhuri et al, 1991). We additionally measured the PI of the SMA blood velocity waveforms.…”
Section: Discussionmentioning
confidence: 66%